Organic products an alternative choice for curing cand healthy lifestyle / Satrinah Muhmin and Nur Azeera Saadon - Muhmin, Satrinah; Saadon, Nur Azeera (2018)
This research presents the benefits of organic produce as an alternative choice to cure disease and healthy lifestyle. The study identifies the benefits carry by organic product to reduce the risk of health problems. The objectives of this research are, first, focused on the customer that purchasing organic product and determine the factors that influence them to consume it. Second, identifying who are the organic vendors in Kota Kinabalu area. As a result, the quality of organic products become the main reason for the consumption as it is free from any chemical residues which harmful to the human body and the environment. Indeed, the organic product helps to reduce chronic diseases such as cancer, coronary heart disease, and others. In essence, this study signifies that going for organic helps the society to have a healthy lifestyle and led to the development of organic vendors in Malaysia.